2015 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2015
DOI: 10.1109/icassp.2015.7178146
|View full text |Cite
|
Sign up to set email alerts
|

Fixed point optimization of deep convolutional neural networks for object recognition

Abstract: Deep convolutional neural networks have shown promising results in image and speech recognition applications. The learning capability of the network improves with increasing depth and size of each layer. However this capability comes at the cost of increased computational complexity. Thus reduction in hardware complexity and faster classification are highly desired. This work proposes an optimization method for fixed point deep convolutional neural networks. The parameters of a pre-trained high precision netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
103
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(114 citation statements)
references
References 11 publications
1
103
0
Order By: Relevance
“…Seide et al showed how to quantize the gradients using only one bit per value to train a DNN using Stochastic Gradient Descent without loss of accuracy [35]. Anwar et al also consider using di↵erent precisions per-layer for LeNet and Convnet [2]. They use linear quantization and retraining to achieve smaller precisions and improve the accuracy of the network.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Seide et al showed how to quantize the gradients using only one bit per value to train a DNN using Stochastic Gradient Descent without loss of accuracy [35]. Anwar et al also consider using di↵erent precisions per-layer for LeNet and Convnet [2]. They use linear quantization and retraining to achieve smaller precisions and improve the accuracy of the network.…”
Section: Related Workmentioning
confidence: 99%
“…Recently, Judd et al and Anwar et al observed that the required representation length varies significantly across DNN layers with the worst-case representation length being much longer than the average length needed [21,2]. This behavior persists across multiple data inputs suggesting that a perlayer choice can be made safely without sacrificing overall accuracy.…”
Section: Introductionmentioning
confidence: 97%
“…Thus, it is to no surprise that several techniques exist for "pruning" or "sparsifying" CNNs (i.e., forcing some model weights to 0) to both compress the model and to save computations during inference. Examples of these techniques include: iterative pruning and retraining ( [3,9,4,27,20]), Huffman coding ( [6]), exploiting granularity ( [18,5]), structural pruning of network connections ( [32,19,1,22]), and Knowledge Distillation (KD) ( [11]).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we seek to answer some fundamental questions that relate to the trade-off between sparsity and inference accuracy: (1) To what extent a CNN can be sparsified without retraining while maintaining a reasonable inference accuracy, (2) What are good model-independent methods for sparsifying CNNs, and (3) Can such sparsification benefit from autotuning [8,2]. We focus on sparsification leaving the actual exploitation of the resulting sparsity to future work.…”
Section: Introductionmentioning
confidence: 99%
“…Retrain each BNN for maximally M epochs. 2 Ensemble Pass: 3 for k=1 to K do 4 Sampling a new training set given weight u i of each example i; 5 for epoch=1 to M do 6 Forward Pass: 7 for l=1 to L do 8 for each filter in l-th layer do…”
mentioning
confidence: 99%